Pengaruh Integritas, Spiritualitas, Budaya, dan Motivasi Kerja Terhadap Kinerja Pegawai di Sekolah Mutiara. - L. Widayati; I.G.K.A. Sunu; I.P.W. Ariawan (Jurnal Administrasi Pendidikan Indonesia, 2023)
This study aims to determine the effect of integrity, spirituality, culture, and work motivation on employee performance. The sample of this research is 40 employees at Mutiara School. This study used an ex-post facto design using descriptive statistical data analysis techniques, simple correlation, partial correlation, multiple correlation, and multiple regression. The results showed that: 1) There is a positive and significant influence between integrity and employee performance with a positive B value of 0.699 and a sig value of 0.001 , 2) There is a positive and significant influence between spirituality and employee performance with a positive B value of 0.657 and a sig value of 0.003, 3) There is a positive and insignificant influence between culture and employee performance with a positive B value of 0.137 and a sig value of 0.437, 4) There is a positive and insignificant influence between work motivation and employee performance with a A positive B is 0.088 and a sig value is 0.425. 5) Simultaneously there is a positive and significant correlation between integrity, spirituality, culture, work motivation and employee performance of 37.587.